TRANSFORMASI DIGITAL LAYANAN ADMINISTRASI MELALUI SOSIALISASI WEBSITE KERJA PRAKTIK DAN TUGAS AKHIR TEKNIK INDUSTRI ITEBA - Elsa Sri Erjuni Rumapea; Elsa Putri Pertiwi; Amirah Nova Khairiyah Pane; Ibnu Anugrah; Rina Agustina; I Made Dwika Parama Yudha; Arei Yovano; Dava Raihan Putra (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2026)
The digital transformation of academic administration services represents a critical requirement for enhancing the effectiveness and efficiency of higher education management. A primary challenge confronting the Industrial Engineering Study Program is the underutilization of the Work Practice (KP) and Final Project (TA) websites, compounded by the absence of standardized formats for administrative submissions, which continue to be processed via email. Such conditions contribute to processing delays, administrative errors, and an escalating workload for administrative staff. This community service initiative aims to advance the digital transformation of administrative services through the socialization of the KP and TA website and the standardization of administrative submission formats. The implementation employed an educational and participatory approach encompassing needs identification, material development, website socialization, and technical assistance, as well as monitoring and evaluation. The findings demonstrate a significant improvement in students’ and lecturers’ understanding of the KP and TA website, greater uniformity in administrative submission formats, and an enhanced potential for service efficiency. This initiative contributes to the optimal utilization of information systems and the cultivation of a digital literacy culture within the industrial engineering study program.